RESPONS PERTUMBUHAN DAN PRODUKSI KEDELAI HASIL SELEKSI TERHADAP PEMBERIAN ASAM ASKORBAT DAN INOKULASI FUNGI MIKORIZA ARBUSKULAR DI TANAH SALIN - Muhammad Ardiansyah; Lisa Mawarni; Nini Rahmawati (Jurnal Agroekoteknologi, 2014)
Using of saline land to grow up soybean has constraints such yield decreasing. By using ofsaline tolerant soybean, using ascorbate acid, and inoculation of mychorrizha vesicular arbuscular(MVA) aimed to increasing growth and yield of soybean in saline land.This research was conductedat Kecamatan Percut Sei Tuan Kabupaten Deli Serdang in Februari – Mei 2013, using split split plotdesign with three factors, i.e. variety of saline tolerant soybean (Grobogan no selection andGrobogan F4 selection), giving of ascorbate acid (0 dan 500 ppm) and MVA isolate (MVA type 1,type 2, type 3, type 4 and type 5). Parameter observed were plant height, number of leaves, numberof productive branches, production per plant.The result of the research showed that using of salinetolerant soybean significantly increase all parameters observed. Giving of ascorbate acidsignificantly increase number of productive branches. Inoculation of MVA significantly effect allparameters observed. Interaction between variety of saline tolerant soybean and giving ascorbateacid were not significantly effect all parameters observed. Interaction between variety of salinetolerant soybean and giving of MVA significantly effected number of leaves 5 week after planting(WAP) and production per plant. Interaction between giving of ascorbate acid and MVA were notsignificantly effect all parameters observed. Interaction of three factors were not significantly effectall parameters observed.Keyword : ascorbate acid, michoryza vasicular arbuscular, salinity, soybean